LA RECEVABILITE DE LA CITATION DIRECTE CONTRE LES BENEFICIAIRES DES IMMUNITES EN DROIT CONGOLAIS : CAS DE VIOLENCES SEXUELLES - Yinda, Trésor MOKIANGO (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to Congolese law, all parliamentarians ara protected by the immunities from prosecution to allow them to effectively perform the functions entrusted to them by the State. Consequently, no parliamentarian can be criminally prosecuted by way of a Direct Summons.However, in terms of sexual violence, Law No. 06/018 of July 20, 2006 amending and supplementing the Decree of January 30, 1940 on the Congolese Penal Code in its relevant provisions of article 42 bis, providers that "the official status of the author of an offense relating to sexual violence can in no case exonerate him from criminal responsibility or constitute a reason for reducing the sentence”.For this purpose, since in the face of acts of sexual violence, the parliamentarian loses his official status in accordance with the aforementioned provisions, it is therefore clear beyond a shadow of a doubt that, if the perpetrator of the offense relating to sexual violence, before seeking the parliamentary mandate did not benefit from any privilege of justice as to say that she was an ordinary citizen like all others, and if, she was before her official quality of parliamentarian, liable before a jurisdiction where the Direct Citation is admitted, can then be brought before the said court for the purpose of answering for its criminal acts without mentioning, in terms of defence, the exception drawn from the inadmissibility of the Direct Summons against a beneficiary of immunities.